Rotational motions of the oar (Rowing Biomechanics Newsletter, 2012)
The rotational motions of the oar which were measured with the BioRow 7D wireless sensor are described. The conclusion is that using BioRow 7D wireless sensor brings very valuable information about oar handling skills in rowing and sculling. In the analysed sculler, the blade moves nearly half the distance of the recovery in a semi-squared position, which significantly increases losses on the aerodynamic drag resistance.